Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Kepuasan Pelanggan di RSI Siti Hajar Sidoarjo (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This study aims to determine the effect of Service Quality, Corporate Image, and Customer Loyalty on Customer Satisfaction. This study uses an associative method with a quantitative approach. The sample of this research is VIP inpatient room customers at RSI Siti Hajar. by using purposive sampling technique and obtained 100 respondents. Data analysis using multiple linear regression. The results of this study indicate that service quality (X1) has a positive and significant effect on customer satisfaction (Y) and corporate image (X2) has a positive and significant effect on customer satisfaction (Y). Another result, that together service quality and corporate image have a positive and significant effect on customer satisfaction.